Reviews - Mary Pettice; Kerrie R. H. Farkas; Edward Sullivan; Brad Lucas (Journal of the Assembly for Expanded Perspectives on Learning, 2006)
Reviews Mary Pettice. Writing New Media: Theory and Applications for Expanding the Teaching of Composition. (Ed. Anne Frances Wysocki, Johndan Johnson-Eilola, Cynthia L. Selfe, and Geoffrey Sirc, 2004). Kerrie R. H. Farkas. Writing at the End of the World . (Richard Miller, 2005). Edward Sullivan. Field Notes on the Compassionate Life: A Search for the Soul of Kindness. (Marc Ian Barasch, 2005). Brad Lucas. (Re)Writing Craft: Composition, Creative Writing, and the Future of English Studies. (Tim Mayers, 2005).